(untitled) (Numerus academy review, 2026)
this study aims to determine the size of the negative impact that the Corona epidemic (COVID-19) has had on the global tourism sector, in addition to highlighting the most important initiatives implemented in some countries of the world to support the recovery of the tourism sector. The study concluded that global tourism, in light of the covid-19 pandemic, received severe unprecedented damage, which led to the loss of millions of jobs and a significant decline in the revenues of the global tourism sector.